Engineered Metal Oxide Nanoparticles as Fungicides for Plant Disease Control - Aida R. Cruz-Luna; Alfonso Vásquez-López; Hugo Rojas-Chávez; Manuel A. Valdés-Madrigal; Heriberto Cruz-Martínez; Dora I. Medina (Plants, 2023)
Metal oxide nanoparticles are considered to be good alternatives as fungicides for plant disease control. To date, numerous metal oxide nanoparticles have been produced and evaluated as promising antifungal agents. Consequently, a detailed and critical review on the use of mono-, bi-, and tri-metal oxide nanoparticles for controlling phytopathogenic fungi is presented. Among the studied metal oxide nanoparticles, mono-metal oxide nanoparticles—particularly ZnO nanoparticles, followed by CuO nanoparticles —are the most investigated for controlling phytopathogenic fungi. Limited studies have investigated the use of bi- and tri-metal oxide nanoparticles for controlling phytopathogenic fungi. Therefore, more studies on these nanoparticles are required. Most of the evaluations have been carried out under in vitro conditions. Thus, it is necessary to develop more detailed studies under in vivo conditions. Interestingly, biological synthesis of nanoparticles has been established as a good alternative to produce metal oxide nanoparticles for controlling phytopathogenic fungi. Although there have been great advances in the use of metal oxide nanoparticles as novel antifungal agents for sustainable agriculture, there are still areas that require further improvement.